Impacts of Global Climate Change 2005
DOI: 10.1061/40792(173)376
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Saltwater Intrusion in Response to Sea-Level Rise

Abstract: A two-dimensional numerical model of variable-density groundwater flow and dispersive solute transport was used to predict the extent, rate, and lag time of saltwater intrusion in response to various sea-level rise scenarios. Three simulations were performed with varying rates of sea-level rise. For the first simulation, sea-level rise was specified at a rate of 0.9 mm/yr, which is the slowest rate of sea-level rise estimated by the Intergovernmental Panel on Climate Change (IPCC). After 100 years, the 250 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…TVD simulations better represented the presumed level of hydrodynamic dispersion as evidenced by an improved ability to represent observed salinity variations compared with finite‐difference transport solutions. Related work by Langevin and Hughes (2009) showed that calibration of a highly parameterized salt water intrusion model can result in parameter surrogacy, such as heterogeneity artifacts in the presence of numerical dispersion. These artifacts can be reduced by using high levels of grid resolution or TVD schemes that minimize numerical dispersion and also by using uniform concentration weighting schemes for calibration instead of assigning weights that are proportional to the concentration value.…”
Section: Model Development and Calibrationmentioning
confidence: 99%
“…TVD simulations better represented the presumed level of hydrodynamic dispersion as evidenced by an improved ability to represent observed salinity variations compared with finite‐difference transport solutions. Related work by Langevin and Hughes (2009) showed that calibration of a highly parameterized salt water intrusion model can result in parameter surrogacy, such as heterogeneity artifacts in the presence of numerical dispersion. These artifacts can be reduced by using high levels of grid resolution or TVD schemes that minimize numerical dispersion and also by using uniform concentration weighting schemes for calibration instead of assigning weights that are proportional to the concentration value.…”
Section: Model Development and Calibrationmentioning
confidence: 99%
“…An inland toe migration in the order of 5 km was achieved in the two studies for a 0.5 m sea-level rise. Langevin and Dausman (2005) evaluated the interface movement in response to sea level rise based on the generalized characteristics of the highly permeable Biscayne Aquifer of Broward County, Florida. The seawater intrusion was investigated under three cases of variable annual rates (0.9, 4.8, and 8.8 mm/year) of sea-level rise.…”
Section: Introductionmentioning
confidence: 99%
“…This study uses SEAWAT, a 3D finite difference numerical model Langevin and Dausman (2005), to simulate the variable-density groundwater flow and SWI in Talar aquifer. The SEAWAT (Guo and Langevin 2002) model used in this study incorporates the MODFLOW-2000 (Harbaugh 2005) and MT3DMS (Zheng and Wang 1999), in the GMS 10.2 package.…”
Section: Groundwater Modeling Packagementioning
confidence: 99%
“…Recent studies have predicted an SLR value of between 20 and 82 cm by the year 2100, indicating an extensive inundation of coastal regions (Vermeer and Rahmstorf 2009;IPCC 2013). Langevin and Dausman (2005) anticipated that an SLR of 0.5 m in Florida's coastal aquifers would result in 1.5 km increase in seawater wedge toe penetration in Broward County's unconfined aquifer, whereas the same SLR would result in about 0.4 km saltwater intrusion in the Nile Delta's confined aquifer. Carretero et al (2013) numerically simulated the SLR in Partido de La Costa, Argentina.…”
Section: Introductionmentioning
confidence: 99%